Perlakuan Uap Panas (Vapor Heat Treatment) untuk Disinfestasi Lalat Buah dan Mempertahankan Mutu Buah Belimbing (Averrhoa carambola L.) - Eti Rohaeti; Rizal Syarief; Rokhani Hasbullah (Jurnal Keteknikan Pertanian, 2010)
AbstractThe objectives of this research were to study mortality of carambola fruit fly (B. carambolae D & H) and to study responses of VHT on quality of carambola (A. carambola L). Fruit fly mortality due to heat has been investigated by immersing fruit fly eggs into hot water at temperatures of 40, 43, 46 dan 49oC for 30 minutes and then at temperature of 46.5oC for 0, 5, 10, 15, 20, 25, 30 minutes. Star fruit were treated at temperature of 46.5oC for 5, 15, 30 minutes and then stored in temperatures of 5, 15oC and room temperature (28-30 oC). The result show that mortality has been achieved 100% at temperature more than 43.0oC for 30 minutes and at temperature 46.0oC for more than 15 minutes. VHT had significant influences to decrease the fruit respiration rates, chilling injury, antraknose, to increase the weight loss, color, and soluble solid content. However, there were no significant change in the hardness, water content, vitamin C and organoleptic test. VHT at temperature 46.5oC for 20 up to 30 minutes were effective to kill fruit flies inside carambola and VHT combined by storing in temperature of 15oC were able to maintain carambola quality during storage.Keywords: vapor heat treatment, fruit fly, B. carambolae, carambola, disinfestationDiterima: 1 Februari 2010; Disetujui: 19 April 2010